A review of current timed-AI (TAI) programs for beef and dairy cattle - Colazo, Marcos G. (Canadian Veterinary Medical Association, 2014)
This is a review of the physiology and endocrinology of the estrous cycle and how ovarian physiology can be manipulated and controlled for timed artificial insemination (TAI) in beef and dairy cattle. Estrus detection is required for artificial insemination (AI), but it is done poorly in dairy cattle and it is difficult in beef cattle. Protocols that synchronize follicle growth, corpus luteum regression and ovulation, allowing for TAI, result in improved reproductive performance, because all animals are inseminated whether they show estrus or not. As result, TAI programs have become an integral part of reproductive management in many dairy herds and offer beef producers the opportunity to incorporate AI into their herds. Gonadotropin-releasing hormone-based protocols are commonly used in North America for estrus synchronization as part of a TAI program. Protocols that increase pregnancy rates in lactating dairy cows and suckling beef cows have been developed. Protocols that improve pregnancy rates in heifers, acyclic beef cows, and resynchronized lactating dairy cows are also discussed.